Pedagogical Interpretation of ICT Classes in the Curricula of Integrated Education - Elżbieta Marek; Elżbieta Sałata (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
Using a computer in the process of integrated education offers great possibilities in achieving the effects of teaching. It requires, though, a teacher's commitment and invention. ICT classes in integrated education aim at developing the abilities of using modern information- communication technology. The purpose of the research was to analyze the curricula in integrated education. The aims, content and suggestions regarding ICT classes and ways of assessing knowledge have been analyzed. In order to achieve the aim, thirteen chosen curricula presented on the website of the Centre for Education Development have been taken into account.